PENGARUH DIAMETER PIPA NOZZLE PADA KINERJA TURBIN AIR PELTON SKALA LABORATORIUM - Syaief, Adhiela Noer; Isworo, Hajar; Ivana, reza Taufiqi; Putra, Muhammad Rezki Fitri; Yasin, Muhammad Noor (ELEMEN : JURNAL TEKNIK MESIN, 2024)
Pelton turbine is an energy conversion medium that utilizes flow performance as a driver and produces electrical energy due to the conversion of turbine rotation. The turbine works when the turbine nozzle injects flow towards the tip of the nozzle which leads directly to the inlet surface of the turbine blade. In this research, we know the effect of nozzle diameter on the performance of turbines that produce different electrical power from various parameters, namely: nozzle diameter used; 1", ¾", 1 ½", and ½" with various nozzle opening variations of 20%, 50%, and 100%. The results obtained with a nozzle diameter of ¾" obtained maximum results with a rotation of 177 (rpm), with a power of 5,168 watts and efficiency increased to 5% at each nozzle valve opening. From these results it can be said that the magnitude or size of the nozzle influences the performance of the turbine where the efficiency of the performance is directly proportional to the rotation and power produced.